(untitled) (Movimenta (ISSN 1984-4298), 2018)
An understanding of the physical properties of the water and the physiology of human immersion can help physiotherapists in using hydrotherapy as a tool for facilitating movement and restoring function. This study presents a review of the physical properties and physiologic effects of the water. Scientific evidence is presented, in order to provide basis for the efficiency and importance of aquatic physical therapy